Modelling the Impact of Vaccination on the Control of Measles in Nepal - Pokharel, Anjana; Adhikari, Khagendra; Gautam, Ramesh (The Nepali Mathematical Sciences Report, 2024)
Measles is a highly contagious disease in human caused by virus. Despite the accessibility of successful vaccines, measles outbreaks still occur, presumably because of the lack of compliance with vaccination. We developed a mathematical model to evaluate the effects of vaccines in different age structures particularly focusing on two groups, to control and eradicate the disease, that may help the planner. Using our model, we formulate the basic reproduction number R 0 that determines, whether the disease persists or dies out. In addition, we carry out sensitivity analysis to identify important parameters that can play a significant role in the control and prevention of measles in different groups of individuals. Furthermore, we investigate the behavior of the disease and effect of vaccination on disease dynamics over a long period.